Towards sustainable development : issues of environmental pollution in Bangladesh - Bashar, S. H. M. Abul; Reazuddin, Md. (Dhaka : IUCN, 1990)
Environment Management
Bibliography : p. 41
1997-09-15
Keywords: Pollution; Environment management; Bangladesh